SEARCH FOR EXCITED ELECTRONS USING THE ZEUS DETECTOR - Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Repond, J; Repond, S; Stanek, R; Talaga, R; Thron, J; Arzarello, F; Ayad, R; Bari, G; et al. (1993)
This paper reports a search for excited electrons at the HERA electron-proton collider. In a sample corresponding to an integrated luminosity of 26 nb-1, no evidence was found for any resonant state decaying into e-γ, νW- or e-Z0. Limits on the coupling strength of an excited electron have been determined for masses between 45 and 225 GeV. This study also reports the observation of the wide-angle eγ Compton scattering process.